The Conserved Actinobacterial Two-Component System MtrAB Coordinates Chloramphenicol Production with Sporulation in Streptomyces venezuelae NRRL B-65442 - Som, Nicolle F.; Heine, Daniel; Holmes, Neil A.; Munnoch, John T.; Chandra, Govind; Seipke, Ryan F.; Hoskisson, Paul A.; Wilkinson, Barrie; Hutchings, Matthew I. (Frontiers in Microbiology, 2017)
Streptomyces bacteria make numerous secondary metabolites, including half of all known antibiotics. Production of antibiotics is usually coordinated with the onset of sporulation but the cross regulation of these processes is not fully understood. This is important because most Streptomyces antibiotics are produced at low levels or not at all under laboratory conditions and this makes large scale production of these compounds very challenging. Here we characterise the highly conserved actinobacterial two-component system MtrAB in the model organism Streptomyces venezuelae and provide evidence that it coordinates production of the antibiotic chloramphenicol with sporulation. MtrAB are known to coordinate DNA replication and cell division in Mycobacterium tuberculosis where TB-MtrA is essential for viability. We were unable to delete mtrA in S. venezuelae unless another copy was present in trans but deletion of mtrB resulted in a global shift in the metabolome, including constitutive, high-level production of chloramphenicol. We found that chloramphenicol is detectable in the wild type strain, but only at very low levels and only after it has sporulated. ChIP-seq showed that MtrA binds upstream of DNA replication and cell division genes and genes required for chloramphenicol production. dnaA, dnaN, oriC and wblE (whiB1) appear to be targets for MtrA in both M. tuberculosis and S. venezuelae. Intriguingly, over-expression of TB-MtrA and gain of function TB- and Sv-MtrA proteins in S. venezuelae also switched on high level production of chloramphenicol. Given the conservation of MtrAB, these constructs might be useful tools for manipulating antibiotic production in other filamentous actinomycetes.